The Impact of SCRM strategies on supply chain resilience: A quantitative study in the Moroccan manufacturing industry - Zineb Elandaloussi; Brahim Benbba; Houdaifa Ameziane (International Journal of Supply Chain Management, 2017)
Both Supply Chain Risk Management (SCRM) and Supply Chain Resilience (SCRES) are emerging topics in the field of supply chain management which require more empirical studies. Many authors have tried to explore the antecedents of SCRES; they have all stressed the role of three main supply chain reduction strategies in achieving SCRES:flexibility, redundancy and collaboration. This article aims to study, through a quantitative study conducted in the Moroccan manufacturing industry context, the hypothetical links between the four constructs of our conceptual model. Data was analyzed using exploratory then confirmatory factor analysis using partial least squares technique of structural equation modelling (PLS-SEM)